2018
DOI: 10.1186/s12891-018-2207-3
|View full text |Cite
|
Sign up to set email alerts
|

Skull-femoral traction after posterior release for correction of adult severe scoliosis: efficacy and complications

Abstract: BackgroundIt is a great challenge for spine surgeons to correct severe rigid scoliosis. We developed a three- staged correction (one stage posterior release and screw placement, two stage skull-femoral traction and three stage posterior instrumentation) for adult severe scoliosis. The objective of this study is to investigate safety and efficacy of a three- staged correction for adult severe scoliosis.MethodsA retrospective review was performed for patients with severe scoliosis receiving three- staged correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The inclusion of skull-femoral traction among potentially dangerous maneuvers was based on studies reporting either frequent MEP deteriorations probably caused by spinal cord ischemia because of stretching of the anterior spinal artery 17 or neurologic deficits associated with this procedure. 18 The relationship between intraoperative MEP changes and the risk of IPNMDs was null in 424 surgeries, showing no significant MEP deteriorations. This finding is consistent with the general consensus that false-negatives are extremely rare in MEP-NIOM.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The inclusion of skull-femoral traction among potentially dangerous maneuvers was based on studies reporting either frequent MEP deteriorations probably caused by spinal cord ischemia because of stretching of the anterior spinal artery 17 or neurologic deficits associated with this procedure. 18 The relationship between intraoperative MEP changes and the risk of IPNMDs was null in 424 surgeries, showing no significant MEP deteriorations. This finding is consistent with the general consensus that false-negatives are extremely rare in MEP-NIOM.…”
Section: Discussionmentioning
confidence: 96%
“…The inclusion of skull–femoral traction among potentially dangerous maneuvers was based on studies reporting either frequent MEP deteriorations probably caused by spinal cord ischemia because of stretching of the anterior spinal artery 17 or neurologic deficits associated with this procedure. 18…”
Section: Discussionmentioning
confidence: 99%
“…HFT is a foundation for intraoperative orthopaedic treatments and reduces the risks of neurological problems; the patient's neurological status is often examined and evaluated. Compared to HGT, HFT could offer more efficient correction of severe spinal deformities, and these factors were considered as follows [ 25 , 26 ]: (1) HFT provided more traction forces and better release for both major and compensatory curves and required less traction time compared to HGT; (2) HFT could let patients obtain more effective traction time and efficacy, especially under the condition of sleep or muscle relaxation; and (3) HFT could be maintained during surgery for further release and correction,…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are several options for the treatment of severe and rigid scoliosis, including surgical correction after traction [6], anterior release and posterior spinal fusion [7], high grade osteotomy [5], and one-stage posterior spinal correction and fusion [8]. Halo-gravity, halopelvic, and skull-femoral traction are usually used to treat severe and rigid scoliosis before or during surgery [9][10][11][12]. Although this technique has a certain corrective effect, patients may not tolerate the long treatment cycle, as well as traction-related complications with an incidence of 16% to 28% [5,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Halo-gravity, halopelvic, and skull-femoral traction are usually used to treat severe and rigid scoliosis before or during surgery [9][10][11][12]. Although this technique has a certain corrective effect, patients may not tolerate the long treatment cycle, as well as traction-related complications with an incidence of 16% to 28% [5,12,13]. Besides, several studies have found that preoperative traction does not increase the final correction rate compared with one-stage spinal fusion.…”
Section: Introductionmentioning
confidence: 99%